Analisis Sentimen terhadap Jalan Rusak di Palembang Pada Media Sosial Menggunakan Algoritma Naïve Bayes - Virgiansyah, Muhammad Rifqi; Stephanie, Stephanie; Rizky Pribadi, Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
In developed countries, the development of road infrastructure plays a vital role in driving economic development. The involvement of public authorities is very necessary in providing funds for infrastructure development, considering that roads are a very important form of public infrastructure. However, there are still some areas, such as Palembang, where damaged roads are still a serious problem. The Palembang regional government is suspected of being less proactive in improving road infrastructure in their area. In an effort to fight for the government's attention to road conditions in Palembang, the public uses social media as a means to voice complaints. A number of tweets, posts, and submissions using the keyword